Looking beyond the R&D effects on innovation: The contribution of non-R&D activities to total factor productivity growth in the EU - Jesus Lopez-Rodriguez; Diego Martinez (European Regional Science Association (ERSA), 2015)
Although non-R&D innovation activities account for a significant portion of innovation efforts carried out across very heterogeneous economies in Europe, how to incorporate them in to economic models is not always straightforward. For instance, the traditional macro approach to estimating the determinants of total factor productivity (TFP) does not handle them well. To counter these problems, this paper proposes applying an augmented macro-theoretical model to estimate the determinants of TFP by jointly considering the effects of R&D and the impact of non-R&D innova- tion activities on the productivity levels of ?firms. Estimations from a model of a sample of EU-26 countries covering the period 2004-2008 show that the distinction between R&D and non-R&D eects is significant for a number of diffffrent issues. First, the results show a sizable impact on TFP growth, as the impact of R&D is twice that of non-R&D. Second, absorptive capacity is only linked to R&D endowments. And third, the two types of endowments cannot strictly been seen as complementary, at least for the case of countries with high R&D intensities or high non-R&D intensities.
Keywords: O0; O3; O4; 330; TFP; R&D; non-R&D expenditures; EU countries